New Homogeneous And Robust Catalyst for Heck and Suzuki Reactions - B. Mirza; M. H. Sayahi (Journal of Sciences, Islamic Republic of Iran)
In this work, different ethyl 2,4-dioxo-4-arylbutanoate derivatives were prepared and evaluated for their Src Kinase inhibitory activity. For this purpose, the appropriate substituted acetophenone derivatives reacted with diethyl oxalate in the presence of sodium ethoxide in dried ethanol to give the corresponding products. All compounds showed moderate activities comparing with staurosporine as the reference drug.